Garlic powder attenuates pulmonary hypertension in broiler chickens: an electrocardiographic-based study - ZAREI, H; SIAHPOUST, S (Journal of the Hellenic Veterinary Medical Society, 2022)
One of the most severe health-threatening issues in broiler chickens is believed to be pulmonary hypertension, characterized by inadequate oxygen levels in blood, elevated workload of the cardiopulmonary network, right ventricle hypertrophy, and death. A total of 180 one-day-old male chickens were dividedinto four equal groups, with 3 replicates per group (45 birds per group, 15 birds per replicate). To induce pulmonary hypertension syndrome, triiodothyronine was added to their diet. A corn-soy based feed was formulated for all treatment groups, and birds were treated with different doses of dietary garlic powder (0.2%, 0.6%, and 1%) for 49 days.Right ventricle/total ventricles (RV/TV), RV/body weight, TV/body weight ratio,and electrocardiographic records were assessed. RV to TV ratio was significantly reduced in all treatment groups at 49 days of age (P <0.05). The S-wave amplitude was decreased significantly (0.2% and 1% garlic powder groups, lead II; and all treatment groups, lead aVF) at 49 days of age. R-wave amplitude showeda significant reduction at 49 days of age (0.6% and 1% garlic powder receivers, lead aVR; all treatment groups, lead II) (P<0.05). QT interval showed a significant increase at 14 days (0.2% garlic powder group, lead III) and at 49 days (0.6% garlic powder group, lead II) (P<0.05). RR interval at 49 days of age (0.6% and 1% treatment groups, lead II; and1% garlic powder receivers, leads III, aVR, and aVF) showed a significant increase compared with controls (P<0.05).According to our study, garlic powder canimprove the electrocardiographic patterns and reversethe detrimental effects offree radicals and oxidative stress in birds withpulmonary hypertension.